HUBUNGAN IMT (INDEKS MASSA TUBUH), JUMLAH KEHAMILAN DAN RIWAYAT HIPERTENSI AKIBAT KEHAMILAN DENGAN KEJADIAN HIPERTENSI DALAM KEHAMILAN DI PUSKESMAS MARTAPURA 1 - Rusdiana, Rusdiana; Rusdi, Rusdi; Zubaidah, Zubaidah; Restu Putra Kamanda (Bajang Institute, 2026)
Hypertension in pregnancy is a condition in which blood pressure increases to ≥140/90 mmHg during pregnancy. It remains one of the leading causes of maternal morbidity and mortality in Indonesia. Risk factors include body mass index, number of pregnancies, and a history of hypertension in previous pregnancies. This study aimed to determine the relationship between body mass index, number of pregnancies, and history of pregnancy-induced hypertension with the incidence of hypertension in pregnancy, specifically at Puskesmas Martapura 1. The study used a quantitative approach with a cross-sectional design. From a total population of 296 pregnant women, 174 were selected using purposive sampling. Data were collected using an observation sheet and analyzed using the Spearman’s rho test. The results showed that the majority of respondents were overweight, had ≤2 pregnancies, and had no history of hypertension in previous pregnancies. The Spearman’s rho test indicated that body mass index (p = 0.831) and number of pregnancies (p = 0.070) had no significant relationship with the incidence of hypertension in pregnancy. However, a history of pregnancy-induced hypertension showed a significant association (p = 0.000). These findings suggest that a history of hypertension in pregnancy is an important factor to consider. Therefore, pregnant women with such a history should be more vigilant and regularly monitor their blood pressure to prevent recurrence